MAPPING JARINGAN KOMUNIKASI “SAYA GOLPUT” DALAM PEMILIHAN UMUM 2019 DI TWITTER (Jurnal Ilmu Komunikasi, 2020)
Mapping "Saya Golput" on active Twitter users in stating abstention from the 2019 general election became the purpose of analysis in research using social network analysis methods. This research departs from the post-positivism paradigm which is used as quantitative research that addresses social reality as something complex, meaningful, holistic, dynamic and interactive interpersonal relationships. The results of this study found interactive communication on Twitter, which is so massive and often discussed the issue of "Saya Golput" because it was triggered by the momentum of general political elections on 17 April 2019, so that the communication mapping communication one to many in the concept of social network analysis in Twitter provides the process of distributing "Saya Golput" information. Trending "Saya Golput" is also marked by public participation in political discussion on Twitter which is increasing. Thus, the "Saya Golput" communication network is equated with apathy and alienation towards politics and the state.